EFFECT OF ORGANIC FERTILIZER AND BORON FOLIAR ON QUANTITATIVE AND QUALTITATIVE TRAITS POTATO FOR PROCESSING - U. B. SHAKER,; I. J. ABDUL RASOOL, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
A field experiment was carried out at University of Baghdad, College of Agricultural Engineering Sciences during fall season of 2020 and spring season of 2021. This study was aimed evaluate the effect of the organic fertilizer and boron foliar on the yield of potatoes for processing. The factorial experiment (5*4) within RCBD and three replicates. The organic fertilizer as palm peat at four levels (0, 12, 24 and 36 ton. ha-1) in addition to the chemical fertilizer recommendation treatment. Boron at four Concentrations 0, 100, 150 and 200 mg. L-1 . The results revealed significant different among application of organic fertilizer at the level of 24 ton. ha-1 and the foliar application of boron at a concentration of 100 mg. L-1 in the leaves area (105.65 and 159.63 dm2 plant-1 for both seasons, respectively), the tubers number, yield and TSS reached 13.78 tubers. plant-1, 9.27 tubers. plant-1 and 833.3 g. plant-1 1122.2 g. plant-1 and 6.67, 5.43% respectively. While the highest tubers dry weight recorded the significant value at the application of 36 ton. ha-1 with foliar application of boron at 150 mg. L-1  reached 21.30 and 26.02% for both seasons, respectively. Also, starch and the specific density of tubers were increased (14.98 and 19.19%) and (1.085 and 1.108%) for both seasons, respectively.